Haemagglutination activity of lectins from extracts of some Vietnam marine sponges - Hung, Le Dinh; Thanh Trung, Dinh (Vietnam Journal of Biotechnology, 2020)
Aqueous extracts from 16 species of Vietnam marine sponges were examined for haemagglutination activity using native and enzyme-treated different animal and human erythrocytes. Among these, extracts from 14 species were found to have haemagglutinination activities toward at least one type of erythrocyte tested meaning that 87.5% of the surveyed marine sponge species possess haemagglutination activity. Strong activity was detected in extracts from marine sponge species Acanthella cavernosa, Axinyssa sp., Cinachyrella sp., 01NT.2.4, 3.5, 3.10, 3.11 and 3.18 with enzyme-treated various animal and human erythrocytes. In a haemagglutination–inhibition test with various monosaccharides and glycoproteins, haemagglutination activity of the extract from A. cavernosa had no affinity for any of the monosaccharides, but inhibited by porcine stomach mucin and fetuin, whereas activities of the extract from Cinachyrella sp. were strongly inhibited by monosaccharides, such as D-galactose and N-acetyl-D-galatosamine, but not with glycoproteins. The activity of Stylissa flexibilis extract was inhibited by D-galactose, porcine stomach mucin, fetuin and their asialo derivatives, suggesting the presence of lectin specific for O-glycans of this species. The activities of four sponge extracts from A. cavernosa, S. flexibilis, Axinyssa sp. and Cinachyrella sp. were stable over a wide range of pH and temperature. Haemagglutination activities of A. cavernosa, Axinyssa sp. and Cinachyrella sp. extracts were independent of the presence of divalent cations, except for the haemagglutination activity of extract from S. flexibilis, which was dependent on the presence of divalent cations. The results suggest that Vietnam marine sponges may be good sources of useful lectins for biochemical and biomedical applications.